Phospholipase A1-based cross-reactivity among venoms of clinically relevant Hymenoptera from Neotropical and temperate regions - Perez-Riverol, Amilcar [UNESP]; Fernandes, Luís Gustavo Romani; Musacchio Lasa, Alexis; dos Santos-Pinto, José Roberto Aparecido [UNESP]; Moitinho Abram, Débora; Izuka Moraes, Gabriel Hideki [UNESP]; Jabs, Frederic; Miehe, Michaela; Seismman, Henning; Palma, Mario Sergio [UNESP]; de Lima Zollner, Ricardo; Spillner, Edzard; et al. (Elsevier, 2018)
Molecular cross-reactivity caused by allergen homology or cross-reactive carbohydrate determinants (CCDs) is a major challenge for diagnosis and immunotherapy of insect venom allergy. Venom phospholipases A1 (PLA1s) are classical, mostly non-glycosylated wasp and ant allergens that provide diagnostic benefit for differentiation of genuine sensitizations from cross-reactivity. As CCD-free molecules, venom PLA1s are not causative for CCD-based cross-reactivity. Little is known however about the protein-based cross-reactivity of PLA1 within vespid species. Here, we address PLA1-based cross-reactivity among ten clinically relevant Hymenoptera venoms from Neotropical and temperate regions including Polybia paulista (paulistinha) venom and Vespula vulgaris (yellow jacket) venom. In order to evaluate cross-reactivity, sera of mice sensitized with recombinant PLA1 (rPoly p 1) from P. paulista wasp venom were used. Pronounced IgE and IgG based cross-reactivity was detected for wasp venoms regardless the geographical region of origin. The cross-reactivity correlated well with the identity of the primary sequence and 3-D models of PLA1 proteins. In contrast, these mice sera showed no reaction with honeybee (HBV) and fire ant venom. Furthermore, sera from patients monosensitized to HBV and fire ants did not recognize the rPoly p 1 in immunoblotting. Our findings reveal the presence of conserved epitopes in the PLA1s from several clinically relevant wasps as major cause of PLA1-based in vitro cross-reactivity. These findings emphasize the limitations but also the potential of PLA1-based HVA diagnostics.
Keywords: Cross-reactivity; Insect venom allergy; Molecular diagnosis; Phospholipase A1; Sensitization